Wages : a workers' education manual - International Labour Office (Geneva : International Labour Office, 1968)
This manual is aimed to explains the main principles and facts in wages in relation to the international labor office rules of engagement.
Includes bibliographical references: p. 251-255.
asm 14/02/2019
Loans
Keywords: Wages